EVALUATION OF GUIDANCE AND CAREER PLANNING COURSE CURRICULUM ACCORDING TO STAKEHOLDERS' OPINIONS - Serdar ERDEM (Fırat University, 2020)
The aim of this research is to evaluate the 8th Grade Guidance and Career Planning Course Curriculum according to the stakeholders’ opinions. In this research in which case study, one of the qualitative research methods, was used, data were collected by two different data collection methods. First of all, a document analysis was conducted on the Guidance and Career Planning Course Curriculum, which was published by the Board of Education and the main components of the curriculum-objectives, content, curriculum experience and evaluation- were examined. Afterwards, class guidance teachers and school counselors were interviewed in order to gather stakeholder opinions on the curriculum. In addition, class guidance teachers, school counselors, 8th grade students and 8th grade students’ parents were interviewed in order to gather stakeholder opinions on implementation of the curriculum. According to the results obtained from the research, it was observed that the opinions of the class guidance teachers and school counselors, who reported their positive and negative opinions regarding the program, overlapped to a large extent and their negative opinions were more dominant. On the other hand, similar results were obtained when the opinions of the class guidance teachers, school counselors, students and parents on the implementation of the program were examined. Although the program stakeholders stated that the course was an important and useful lesson, they expressed more negative opinions on the curriculum implementation. The teachers, students and parents in the stakeholder groups stated that the weekly course duration was inadequate, that class guidance teachers were insufficient for this course, that the participation of parents in the process was poor, that 8th grade wasn’t suitable for the implementation of the curriculum, that the explanations in the curriculum were insufficient, that the class sizes were big for the implementation, that the number of tests performed was insufficient and that the tests performed were not beneficial.